Estimation of Compositions of Zr-Cu Binary Sputtered Film and Its Characterization - Katsuyoshi Kondoh; Junji Fujita; Junko Umeda; Tadashi Serikawa (Advances in Materials Science and Engineering)
Zr-Cu amorphous films were prepared by radio-frequency (RF) magnetron sputtering on glass substrate using two kinds of the elemental composite targets: Cu chips on Zr plate and Zr chips on Cu plate. It was easy to precisely control chemical compositions of sputtered films by selecting the chip metal and the number of chips. It is possible to accurately estimate the film compositions by using the sputtered area and the deposition rate of Cu and Zr. XRD analysis on every as-sputtered film showed the broadened pattern. Zr-rich composition film, however, revealed a small peak at the diffraction angle of 2𝜃=35∘, and Cu-rich one indicated it at 2𝜃=43∘. TEM and electron diffraction analysis on the former also showed the main Zr ring patterns and its streaks. Zr-rich composition film with Cu content of 34 at% or less indicated a good corrosion resistance by salt spray test. On the other hand, Cu-rich version with 74 at% Cu or more was poor in corrosion resistance. This was because Zr was reactively passive, and caused the spontaneous formation of a hard non-reactive surface film that inhibited further corrosion than Cu.